Historia Docet: Reconstructing Historical Consciousness in Secondary Education Through Multiperspectivity and Critical Discourse Analysis - Burhanuddin Burhanuddin (Jurnal Mamangan, 2024)
This qualitative research investigates how multiperspectivity and critical discourse analysis can reconstruct historical consciousness among secondary school students in Indonesia. Conducted across five secondary institutions with 205 student participants and 15 educators, this study employs thematic analysis of interviews, classroom observations, and student essays to examine students' engagement with multiple historical narratives. The research reveals significant disparities in how different historical perspectives—nationalist, colonial-critical, subaltern, international, and gender-based—are integrated into curricula and student consciousness. Findings demonstrate that systematic implementation of multiperspective pedagogy increases critical historical thinking from 45% to 78% among participants, while evidence evaluation competency improves by 52%. The study concludes that Historia Docet—history teaches—requires institutional commitment to pedagogical pluralism, teacher professional development in critical discourse analysis, and curriculum redesign emphasizing narrative multiplicity. These findings have implications for Indonesian secondary education policy, suggesting that historical consciousness is not constructed through monolithic narratives but through iterative engagement with competing perspectives and evidence evaluation.